Factors Affecting Success of Corneal Grafting : An Observational Study - Saif Al-Shamarti (Indian Journal of Forensic Medicine & Toxicology, 2020)
This is an observational study of 32 corneal implantation cases performed by the researcher. It shows thatYounger patients (below 60 years) show more improvement. Female patients show more improvement.Corneal dystrophy cases show more improvement followed by Keratoconus followed lastly bullouskeratopathy. Donors aged below 60 years give results that are more positive. There are mild results that aremore positive if the time between death and transplant is less than 5 days. Trephine size more than 7.5MMshows more improvement. Punch size of 8.25MM shows most improvement. Using General anesthesiashows more improvement